Recent Trends in the Probability of High Out-of- Pocket Medical Expenses in the US - Katherine Baird (Luxembourg Income Study (LIS), 2016)
Objective: This paper measures large out-of-pocket expenses by health condition, income, and elderly status, and estimates changes in them between 2010 and 2013. Data Source: The paper uses nationally-representative household survey data. Study Design: Logistic regression estimates the probabilities of high expenses by demographic groups in the two study years. Households have large out-of-pocket expenses when these exceed 5% or alternatively 10% of income. Data Collection/Abstraction Method: The study uses 99.5% of the 344,000 individuals in the two samples. Principle Findings: Despite favorable conditions, the large numbers of Americans exposed to high out-of-pocket expenditures has not declined much. Conclusions: The magnitude of financial risk and trends in them underscore the need to monitor the ACA's success in reducing Americans' exposure to large medical bills.
Keywords: 330; out-of-pocket; insurance; financing equity; Affordable Care Act